STANDARISASI RESEP RENDANG DAUN SINGKONG DI NAGARI SIJUNJUNG KABUPATEN SIJUNJUNG - Tul ‘Aini, Fitra; Asnur, Lise (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
Fitra Tul 'Aini (2024): Standardization of the Traditional Recipe for Cassava Leaf Rendang in Nagari Sijunjung, Sijunjung Regency. Thesis D4 Hospitality Management, Department of Tourism. Faculty of Tourism and Hospitality, Padang State University. As of right now, Nagari Sijunjung Sijunjung Regency lacks an ordinary recipe. Variations are the cause of this in the amount of ingredients used, the processing method, and the color, texture, flavor, and scent of cassava leaf rendang in this region. The purpose of this study is to develop a universally recognized recipe for Nagari Sijunjung's cassava leaf rendang. This kind of study uses a hybrid methodology that blends quantitative and qualitative data. Five knowledgeable individuals with extensive experience in crafting Cassava Leaf Rendang provided the qualitative data source. Three panelists, who were restricted to UNP Culinary Management lecturers, got the quantitative data source. The methods of collection, reduction, data presentation, and conclusions in qualitative data analysis are as follows. Techniques for analyzing quantitative data employ the formula (Mx = ∑X)/N). The study yielded a single standard formula that included the following parameters: color (very brown), texture (very soft cassava leaves), aroma (very fragrant with Rendang seasoning), and flavor (very tasty cassava leaves). Keywords: Standardization, Recipes, Traditional Specialties, Cassava Leaf Rendang